(3ejRGf GdeYOdI aj TCf GdHSedIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3eMehO UObi s)
(3ChdgG (B:s
(3GdMeO ddg hGdUdGI hGdSdGe Ydi QShd Gddg Udi Gddg Ydjg hSde bO ETJgQ cdGe GdfGS ai TCf GdHSedI hEMJLGLge Ydi CfgG bQBf Ch ZjQ bQBf hTfY GdbGVi CHh HcQ GdHGbdGfi hZjQg Ydi GdTGaYi ai EKHGJgG bQBfkG HCf GdbQBf dGjKHJ CHGdXf s
(3BNQgG (B:s
(3adeG Sde bGd hGdPi faSi HjOg Efi dCTHgce UdGI HQShd Gddg Udi Gddg Ydjg hSde gPG MOjK UMjM dG Ydg dg hgh CUM eG hQO ai GdHGH Hd de jUM ajg MOjK ZjQg GfJgi hddg GdMeO hGdefI ejRGf GdeYOdg ai TCf GdHSedI ddLdGd GdSjhWi s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs